Development of E-Learning Learning Media for Class VII Informatics Subjects at Islamic Middle School Bustanul Hikmah Lamongan - Lukfil Anam; M. Subandowo; M. Hari Karyono (Universitas of Muhammadiyah Makassar, 2022)
Learning media development is essential because learning must continue to innovate so that education will continue to develop with the times. This study aims to describe, explain and analyze the development process, feasibility, and effectiveness of web-based e-learning learning media through blended learning methods for informatics subjects in junior high schools. This study uses the ADDIE development method through 5 stages. Qualitative data were obtained from interviews, input from validators, and documentation. In contrast, quantitative data was obtained from the results of student learning trials before and after using e-learning learning media through blended learning, which was analyzed using a feasibility test. The results of the development show that: (1) Produce website-based e-learning learning media through the ADDIE development stage, (2) The process of testing the feasibility of website-based e-learning learning media through validators of IT/media experts, material/content experts, learning design experts whose results are 95% very feasible and the results of the small group trial the results are also feasible to be tested, (3) The level of effectiveness in website-based e-learning learning media through blended learning can be seen from the feasibility value, the results of which are proven to be effective. This is reinforced by the results of the average value of the student response field trial of 85%. Students are more likely to like the website-based learning model through Blended Learning.